KAJIAN PEMANFAATAN BIJI KOPI (ARABIKA) SEBAGAI BAHAN BAKU PEMBUATAN BIODIESEL - Bella Simbolon, Kartini Pakpahan, Siswarni MZ (Jurnal Teknik Kimia USU, 2013)
This research aims to exploit the coffee seed oil as raw material for biodiesel by esterification process, then followed by transesterification process and studied the influence of variations in the weight ratio of solvent: ground coffee beans in the coffee bean oil extraction process. The methodologies of this researchare conducted on the process of preparation of raw materials, extraction, and testing phase.  Extraction is done with a variety of types of solvent n-hexane (C6H14) and toluene (C7H8 (C6H5CH3)) and a variety of solvents through a ratio of 1:5, 1:6, 1:7 and 1:8 against the mass of each run, which is 40 gram. Another variable is still 2 hours extraction time and temperature solvent extraction with n-hexane (C6H14) (boiling point 690C) is 70-75 0c and the solvent toluene (C7H8 (C6H5CH3))(boiling point 1100C) is 110-1150C. Testing phase is done bythe use of coffee oil esterification process in the molar ratio of methanol: free fatty acid catalyst H2SO4 = 3:1 with 1% v / v for 1hour with stirring 600 rpm and transesterification process at a molar ratio of methanol: oil = 9:1 coffee with 1.75% NaOH catalyst for 2 hours with stirring 600 rpm. Esterification process as conducted preliminary due to high levels of free fatty acids coffeeoils, which is 22.2%. Extraction results include the maximum yield of the coffee oils  17.73% in toluene weight ratio: coffee powder= 6:1, and coffee oil data in the form of the density 93.75 g / ml, viscosity 59.326 cP and fatty acid composition of the highest linoleic acid 40.8765% and palmitic acid 37.4492%. The results of esterification and transesterification obtained by the methyl ester equal to 39.63% with density 0.915 g / ml, 22.5498 cSt kinematic viscosity and flash point 130 0C.